2012
DOI: 10.4103/2278-9626.101359
|View full text |Cite
|
Sign up to set email alerts
|

Parents′ perceptions of factors influencing the oral health of their preschool children in Vadodara city, Gujarat: A descriptive study

Abstract: Objectives: To assess parents′ perceptions about the factors influencing the oral health of preschool children. Materials and Methods: A cross-sectional questionnaire survey was carried out among the parents of the preschool children in Vadodara City, India. A list of preschools was obtained from the Social Science Department of the MS University, Vadodara, India. The study included 828 parents, out of whom 597 responded, with the response rate of 72.10%. Twenty-seven questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
9
11
0
Order By: Relevance
“…A high proportion of the subjects reported that children's bad oral health could affect the general health which implies that their children's oral health should be in a good status, however, this wasn't the case since dmft/DMFT was 4.64/1.08. Similar to previous studies (16, 1820) parents reported that pain was the main reason for visiting the dental office instead of regular check-up.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A high proportion of the subjects reported that children's bad oral health could affect the general health which implies that their children's oral health should be in a good status, however, this wasn't the case since dmft/DMFT was 4.64/1.08. Similar to previous studies (16, 1820) parents reported that pain was the main reason for visiting the dental office instead of regular check-up.…”
Section: Discussionsupporting
confidence: 86%
“…A high percentage of children in the sample were reported to brush their teeth at least once to twice daily, similar results were found in other studies (1416), and the brushing frequency was more when the parents were university educated, similar to that reported by Rajab (17). More than half of the total sample of parents guided and supervised their children while brushing their teeth (Table 2) and this was similar to other's findings (18). The use of additional measures was low in our sample, similar to other studies (16, 19), and this could be attributed to the lack of knowledge of benefits of these auxiliary methods (15, 16, 19, 20).…”
Section: Discussionsupporting
confidence: 86%
“…In similar study carried out by Chhabra et al among 620 parents of pre-school children in India majority were mother (81.3%), 20 but in the study carried out by Thakare et al in Gujarat, India majority (67.5%) were father. 21 This shows that on some society father are more active on taking their child on hospital, while on others mother. Tooth brushing habits, use of fluoridated toothpaste, frequency and duration of tooth-brushing, are the most important factors on oral self-care behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this risk of toxicity, luoride gel treatment is generally not recommended to children below 6years of age. (Ismail and Hasson, 2008;Thakare et al, 2012) Parental knowledge with respect to the irst dental visit of their child, the correct time to start cleaning the child's teeth, a quantity of toothpaste used, cariogenic effects of dietary food, the requisite for luoride treatment etc., needs to be improved (Clark, 1993;Sköld-Larss et al, 1999).…”
Section: Introductionmentioning
confidence: 99%